Students' perception on the factors that affect the effectivenss of LIS 181 (field assignment) - Capil, Shane BL C.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
Field assignment is defined as a practical training for students to gain insight into the various phases of library work (UPSLIS Guidelines for Field Assignment 2009-2010). It has been an integral part of the Library and Information Science curriculum since 1916. However, there are problems arising from the revisions made on the guidelines of the course (LIS 181) since its integration. The main objective of this study is to determine the factors affecting the effectiveness or ineffectiveness of LIS 181 (Field Assignment) from the viewpoint of SLIS students. Specifically, this study aime: a) to know what do students consider more in choosing their institution for field assignment - self-convenience or proper application; b) to discern the differences among various types of library and other related institution in terms of work assignment, training, treatment, and assessment of student trainees; c) to enumerate the typical problems that students experience in their fieldwork; d) to determine the measures students take in order to solve those problems; e) to identify the strengths and weaknesses of the course from the viewpoint of the students in terms of objective(s) of the course, requirements, conduct of the fieldwork, and others, and; f) to reveal the students opinion in regards to meeting the objectives of the course, applying theories into work, gaining knowledge, and developing skills in their chosen institutions.
This study is only limited to the viewpoints of SLIS students who have taken up LIS 181 from AY 2008-2009 to first semester of AY 2010-2011. A self-administered questionnaire was used to gather data and came up with these general findings: 1) Students value both self convenience and proper application factors almost at the same level in choosing their institution for fieldwork, and think that there is nothing wrong with letting them choose their institution for fieldwork; 2) Majority of the respondents said there is/are differences among their institutions for fieldwork and the number one difference(s), tied for the first spot, are phases of work and workload, while ""type of library" is first on the list of factors affecting the difference(s); 3) "Trivial and/or repetitive task"" is the number one problem that practicum students encountered in their institution for fieldwork; 4) Majority of the students, even though aware of the problems they experienced in the place of fieldwork, still chose not to do anything to solve them; 5) A great majority of the students think that the objectives of the course (LIS 181) is sufficient, but they also think that there should be more to be included on the list of requirements; 6) On the list of requirements, students said that journal writing seems problematic in terms of content and time constraints, while they think that the conduct of fieldwork wherein the introductory letter stating the different phases of library and information work sent by the adviser to the supervisor/host institution is deemed sufficient, and; 7) Three quarters of the respondents said that they were able to meet the objectives of the course in, while about half were able to apply the theories they learned in class, and most sere able to gain knowledge and develop their skills all their institution for fieldwork.
Thus, it can be concluded from the overwhelming positive feedback of past LIS 181 students that the current LIS 181 curriculum is perceived as effective.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Occupational training; Employees--Training of